Гематологическое исследование непарного шелкопряда и прогоз его численности - Зелинская, Л.М. (Вестник зоологии, 1968)
At the early stages of Porthetria dispar L. polyhedria a number of trophic cells in hemolymph decreases, young cells — proleucocytes, macronucleocytes and active phagocytes appear. In pupa and butterflies the granulocytes become smaller, a number of granules with nutritious substances considerably falls. In microsporodiosis the pathologic changes in blood are expressed in gemmation and vacuolization of protoplasm and nuclei of macronucleocytes, in appearance of small macro- and micronucleocytes as a result of their intensive division, in the presence of a meronts in protoplasm of some micronucleocytes, in size decrease and exhaustion of granulocytes in pupa. The changes evoked by the desease agent in hemolymph of pupa and butterflies are the most noticeable. That is why the hematologic investigation of populations for prediction of Porthetria dispar L. quantity is better to be conducted at these phases.